The Role of Endonasal Endoscopic Optic Nerve Decompression as the Initial Management of Primary Optic Nerve Sheath Meningiomas - Maza, Guillermo; Subramaniam, Somasundaram; Yanez-Siller, Juan C.; Otto, Bradley A.; Prevedello, Daniel M.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background The management of optic nerve sheath meningiomas (ONSMs) remains controversial. Surgical decompression through traditional resective techniques has been associated with significant morbidity. While radiation therapy, the current modality of choice is not exempt of risks.Transnasal endoscopic optic nerve decompression (EOND) offers a direct route to the orbit, optic canal, and orbital apex, providing a minimally invasive alternative.Objective The main objective of this article is to assess EOND as the initial management of symptomatic patients with primary ONSM.Methods Patients with ONSMs without a history of radiotherapy who underwent EOND were retrospectively reviewed. Postoperative imaging, duration of follow-up, and visual outcomes at the last ophthalmology visit were assessed.Results Four women (age range 25–63 years) with primary ONSMs that underwent EOND were identified. All patients displayed subjective and objective baseline signs of vision loss. Additionally, baseline proptosis, diplopia, optic nerve atrophy, and ocular pain were identified. In none of the cases, the optic nerve sheath was breached.Following EOND, all patients deferred treatment with adjuvant radiotherapy. At a mean postoperative follow-up of 14 months, all patients were clinically stable without evidence of disease progression on imaging or physical examination. At last ophthalmologic evaluation, three out of four showed objective improvements from baseline visual acuity and visual field (remaining patient had baseline optic nerve atrophy).Conclusion These results suggest that EOND could be a viable initial treatment modality of selected primary ONSM cases. Further studies are warranted to determine long-term efficacy and its role in a stepwise progression of management, preceding radiotherapy.
Keywords: orbital tumors; optic nerve sheath meningiomas; endoscopic endonasal approach; endoscopic optic nerve decompression